2012
DOI: 10.1074/jbc.m112.343764
|View full text |Cite
|
Sign up to set email alerts
|

Coiled Coil Domain-containing Protein 56 (CCDC56) Is a Novel Mitochondrial Protein Essential for Cytochrome c Oxidase Function

Abstract: Background: Cytochrome c oxidase (COX), the final enzyme of the mitochondrial electron transport chain, requires several assembly factors for its proper function. Results: ccdc56 knock-out flies showed developmental delay, lethality, and a dramatic decrease in the levels/activity of COX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…hCOA3 Is a Transmembrane Protein of the Inner Mitochondrial Membrane-We have recently shown CCDC56 to be a mitochondrial protein essential for COX activity in D. melanogaster (20), although its precise function remained to be elucidated. BLAST alignments showed this protein is well conserved from Drosophila to humans, and more recent studies have suggested CCDC56 is the homologue of yeast Coa3 (18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…hCOA3 Is a Transmembrane Protein of the Inner Mitochondrial Membrane-We have recently shown CCDC56 to be a mitochondrial protein essential for COX activity in D. melanogaster (20), although its precise function remained to be elucidated. BLAST alignments showed this protein is well conserved from Drosophila to humans, and more recent studies have suggested CCDC56 is the homologue of yeast Coa3 (18).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial Subfractionation and Proteinase K Protection Assays-Mitochondria were purified from HeLa cells expressing hCOA3-FLAG as described previously (20). Mitochondria were ruptured by sonication.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations